PENGARUH MASA KERJA, PELATIHAN, MOTIVASI, PENILAIAN KINERJA, KOMPENSASI DAN KINERJA PEGAWAI TERHADAP PRODUKTIVITAS KERJA (Studi Kasus Pada PT.Brantas Abipraya(Persero)) - Djoko Menutomo; Aloysius Harry Mukti; Susi Adiawaty (Magister Manajemen Institut Bisnis Nusantara, 2022)
This study aims to examine the tenure, training, motivation, performance appraisal, compensation and employee performance on work productivity. This study uses quantitative methods with the Smart-PLS 3.0 software tool to process questionnaire data. The sample in this study amounted to 92 employee respondents consisting of two units, namely business units consisting of operations division 1, operations division 2 and operating division 3, equipment and precast units, Abipraya Properti and Brantas Energi units and work units consisting of the marketing department, production, finance, human capital, business development, QHSE, internal control unit and corporate secretary. The results of the study show that tenure, work appraisal and performance have a positive effect on work productivity. Training has a negative effect on work productivity. Motivation and compensation have no effect on work productivity.